Surveillance for Onchocerciasis-Associated Epilepsy and OV16 IgG4 Testing of Children 6–10 Years Old Should Be Used to Identify Areas Where Onchocerciasis Elimination Programs Need Strengthening - Alfred Dusabimana; Joseph Nelson Siewe Fodjo; Michel Mandro Ndahura; Bruno P. Mmbando; Stephen Raimon Jada; Annelies Boven; Eric De Smet; Tony Ukety; Alfred K. Njamnshi; Anne Laudisoit; Steven Abrams; Robert Colebunders (Pathogens, 2022)
To eliminate onchocerciasis-associated morbidity, it is important to identify areas where there is still high ongoing Onchocerca volvulus transmission. Between 2015 and 2021, door-to-door surveys were conducted in onchocerciasis-endemic villages in Cameroon, the Democratic Republic of Congo (DRC), Nigeria, South Sudan, and Tanzania to determine epilepsy prevalence and incidence, type of epilepsy and ivermectin therapeutic coverage. Moreover, children aged between six and 10 years were tested for anti-Onchocerca antibodies using the Ov16 IgG4 rapid diagnostic test (RDT). A mixed-effect binary logistic regression analysis was used to assess significantly associated variables of Ov16 antibody seroprevalence. A high prevalence and incidence of epilepsy was found to be associated with a high Ov16 antibody seroprevalence among 6–10-year-old children, except in the Logo health zone, DRC. The low Ov16 antibody seroprevalence among young children in the Logo health zone, despite a high prevalence of epilepsy, may be explained by a recent decrease in O. volvulus transmission because of a decline in the Simulium vector population as a result of deforestation. In the Central African Republic, a new focus of O. volvulus transmission was detected based on the high Ov16 IgG4 seropositivity among children and the detecting of nodding syndrome cases, a phenotypic form of onchocerciasis-associated epilepsy (OAE). In conclusion, Ov16 IgG4 RDT testing of 6–10-year-old children is a cheap and rapid method to determine the level of ongoing O. volvulus transmission and to assess, together with surveillance for OAE, the performance of onchocerciasis elimination programs.